2021
DOI: 10.5505/pajes.2020.03083
|View full text |Cite
|
Sign up to set email alerts
|

Determination and economic analysis of the optimum insulation thickness of building walls, considering annual CO2 emission

Abstract: Binalarda kullanılan enerji tüketiminin yaklaşık olarak %70-80'i ısıtma, soğutma ve sıcak su üretimi amaçlıdır. Binalarda enerji tasarrufu için alınabilecek başlıca önlemlerden birisi ısı yalıtımıdır. Bu çalışmada Denizli ili için kış aylarında binaların ısıtılması ve yaz aylarında soğutulmasında enerji tasarrufu için farklı yakıt türlerinde optimum izolasyon kalınlıkları arasındaki en ekonomik kombinasyonun belirlenmesinde farklı izolasyon malzemeleri ve CO2 emisyonları dikkate alınarak karşılaştırmalı bir ça… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A significant number of studies are done with just one city regardless of the climatic region in Turkey. For example, in Malatya [10], Denizli [15,18,22], Erzurum [17], İstanbul [20], Bilecik [23], Bursa [24], İzmir and Ankara [25], Diyarbakır [26]. Moreover, some studies are carried out by selecting only one [27][28][29][30][31][32][33][34][35][36] or more [11][12][13][37][38][39] cities from each climatic zone; furthermore, by merely opting for cold towns [9,14] in Turkey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of studies are done with just one city regardless of the climatic region in Turkey. For example, in Malatya [10], Denizli [15,18,22], Erzurum [17], İstanbul [20], Bilecik [23], Bursa [24], İzmir and Ankara [25], Diyarbakır [26]. Moreover, some studies are carried out by selecting only one [27][28][29][30][31][32][33][34][35][36] or more [11][12][13][37][38][39] cities from each climatic zone; furthermore, by merely opting for cold towns [9,14] in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Şahin et al [22] presented a comparative study, taking into account the different insulation materials and CO 2 emissions, in determining the most economical combination between the optimum insulation thicknesses in different fuel types for the city of Denizli in Turkey. They observed that the optimum insulation thickness, which makes the cost minimum, varies between 0.012 and 0.031 m for heating in the winter months and 0.009-0.022 m for cooling in the summer months.…”
Section: Introductionmentioning
confidence: 99%